Lohnkostenzuschüsse: Ökonomische Effizienz und gesellschaftliche Akzeptanz - Henning Klodt (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
The persistence of unemployment in Germany calls for innovative instruments in active labour market policy. In recent years, labour economists have suggested several wage subsidisation schemes which could significantly contribute to the reduction of structural unemployment. Although economically efficient, however, the implementation of such schemes is hampered by public concerns which basically reflect a general distrust in market-oriented instruments in the area of social policy. If adjustment pressures on labour markets will continue to rise, this resistance will probably decline.
Keywords: J21; J65; J68; 330